Analysis of prostate intensity‐ and volumetric‐modulated arc radiation therapy planning quality with PlanIQTM. Issue 4 (25th March 2021) - Sasaki, Motoharu; Nakaguuchi, Yuji; Kamomae, Takeshi; Tsuzuki, Akira; Kobuchi, Satoshi; Kuwahara, Kenmei; Ueda, Shoji; Endo, Yuto; Ikushima, Hitoshi
Abstract: Purpose: The purpose of this study was to assess the quality of treatment planning using the PlanIQ TM software and to investigate whether it is possible to improve the quality of treatment planning using the "Feasibility dose‐volume histogram (DVH) TM " implemented in the PlanIQ TM software. Methods: Using the PlanIQ TM software, we retrospectively analyzed the learning curve regarding the quality of the treatment plans for 148 patients of prostate intensity‐modulated radiation therapy and volumetric‐modulated radiation therapy performed at our institution over the past eight years. We also sought to examine the possibility of improving treatment planning quality by re‐planning in 47 patients where the quality of the target dose and the dose limits for organs at risk (OARs) were inadequate. The re‐planning treatment plans referred to the Feasibility DVH TM implemented in the PlanIQ TM software and modified the treatment planning system based on the target dose and OAR constraints. Results: Analysis of the learning curve of the treatment plans quality using PlanIQ TM software retrospectively showed a trend of improvement in the treatment plan quality from year to year. The improvement in the treatment plans quality was more influenced by dose reduction in the OARs than by target coverage. In all cases where re‐planning was performed, the improvement in the treatment plan's quality resulted in a better treatment plan than the one adopted for delivery to patients in the clinical plan. Conclusions: The PlanIQ TM provided insights into the quality of the treatment plans at our institution and identified problems and areas for improvement in the treatment plans, allowing for the development of appropriate treatment plans for specific patients.